Sistem Informasi Penjualan Kopi Khas Lampung Berbasis Website - Wahyu Setyaningsih, Putry (INTEK : Jurnal Informatika dan Teknologi Informasi, 2021)
Coffee is one of the agricultural products favored by all levels of society. Lampung is one of the coffee-producing regions in Indonesia. Arabica coffee is a subak abian which is spread throughout the districts in Lampung. The number of coffee shops in major cities in Indonesia not only benefits coffee shop owners, but also encourages coffee farmers in various regions in Lampung to produce even better coffee beans. The emergence of coffee shops also opens up job opportunities for job seekers to be able to work in coffee shops throughout Indonesia. Micro enterprises are the main source of income and job opportunities for the lower class people. The more information technology is developed, the easier it is to promote coffees from certain regions, one of which is coffee from Lampung. The buying and selling activity of coffee is getting easier because you already use internet technology through a website-based sales application. Through a website-based Lampung coffee sales application, coffee shop entrepreneurs and coffee companies can easily sell coffee products. Based on the problems faced, a website-based design of a typical Lampung coffee sales application was made where this Lampung typical coffee sales application is the best solution to solving problems that exist in agriculture in one of the coffee factories in the Lampung area.